Intracranial electroencephalographic biomarker predicts effective responsive neurostimulation for epilepsy prior to treatment. Issue 3 (7th January 2022) - Scheid, Brittany H.; Bernabei, John M.; Khambhati, Ankit N.; Mouchtaris, Sofia; Jeschke, Jay; Bassett, Dani S.; Becker, Danielle; Davis, Kathryn A.; Lucas, Timothy; Doyle, Werner; Chang, Edward F.; Friedman, Daniel; et al.
Abstract: Objective: Despite the overall success of responsive neurostimulation (RNS) therapy for drug‐resistant focal epilepsy, clinical outcomes in individuals vary significantly and are hard to predict. Biomarkers that indicate the clinical efficacy of RNS—ideally before device implantation—are critically needed, but challenges include the intrinsic heterogeneity of the RNS patient population and variability in clinical management across epilepsy centers. The aim of this study is to use a multicenter dataset to evaluate a candidate biomarker from intracranial electroencephalographic (iEEG) recordings that predicts clinical outcome with subsequent RNS therapy. Methods: We assembled a federated dataset of iEEG recordings, collected prior to RNS implantation, from a retrospective cohort of 30 patients across three major epilepsy centers. Using ictal iEEG recordings, each center independently calculated network synchronizability, a candidate biomarker indicating the susceptibility of epileptic brain networks to RNS therapy. Results: Ictal measures of synchronizability in the high‐γ band (95–105 Hz) significantly distinguish between good and poor RNS responders after at least 3 years of therapy under the current RNS therapy guidelines (area under the curve = .83). Additionally, ictal high‐γ synchronizability is inversely associated with the degree of therapeutic response. Significance: This study provides a proof‐of‐concept roadmap for collaborative biomarker evaluation in federated data, where practical considerations impede full data sharing across centers. Our results suggest that network synchronizability can help predict therapeutic response to RNS therapy. With further validation, this biomarker could facilitate patient selection and help avert a costly, invasive intervention in patients who are unlikely to benefit.